Pendidikan Prinsip Keadilan dalam Akuntansi Syariah - Amar, Siti Salama; Pramita Putri, Devi Lestari; Rahmawati, Ria (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2022)
The purpose of this study is the application of the principle of justice in sharia accounting which examines the allocation of profits to stakeholders with the object of Islamic banking research. The research method used in this research is a qualitative descriptive type with the type of data in the form of allocation of company profits referring to financial reports and other data that supports research through interviews with the application of justice principles in sharia accounting. These data are collected and analyzed by comparing the application of the provisions regarding the allocation of profits in Islamic banking with the teachings of Islamic accounting in Islam. The research was conducted at one of the Sharia People's Credit Banks located on Madura Island. The results of the study can be concluded that the financial statements at the Islamic People's Credit Bank (BPRS) have shown a proportional allocation of profits to stakeholders, namely profits have been allocated to owners of funds consisting of customers and shareholders as well as to employees by applying Islamic values ​​in sharia accounting. Implementation refers to education on the principles of justice applied by the BPRS, this can be seen from the allocation of profits to stakeholders who have achieved the value of justice in accordance with Islamic teachings in sharia accounting.